Men Buying Behaviour on Plus Size Jeans Product (Journal of Innovation, Business and Entrepreneurship, 2020)
Based on the data from Warta Pengkajian Perdagangan Volume 3 no. 12 Tahun 2016, the sales of jeans are increasing every year. In Indonesia, the number of obesity is also continuing to keep growing every year, including in Bandung. This phenomenon allows Avant Grande, a big-size jeans company based in Bandung, to step in into the market and get the potential market to increase their big size jeans sales. Avant Grande has been facing sales issues, where their sales didn’t reach its target and did not achieve their expectation. This research aims to find men's purchase decision process on plus-size jeans and also understand men's buying behaviour on plus-size jeans purchasing. The researcher found that the decision-making process of men buying behavior on plus-size started from the firm's attendance state. Then, it will be affected by the purchase environment factor. An environment will influence how the customer chooses the product. Then, men who use plus-size jeans will purchase a product then do a post-purchase activity. Based on the result of the study, men who use large-sized jeans prefer to purchase offline than online. Foreign brands are more preferred products to buy than local brands or tailor because they perceive it as more trusted.Keywords: Men buying behavior, purchase decision, plus size, jeans, SEM PLS